2015
DOI: 10.1186/s13395-015-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Muscular dystrophy in the mdx mouse is a severe myopathy compounded by hypotrophy, hypertrophy and hyperplasia

Abstract: BackgroundPreclinical testing of potential therapies for Duchenne muscular dystrophy (DMD) is conducted predominantly of the mdx mouse. But lack of a detailed quantitative description of the pathology of this animal limits our ability to evaluate the effectiveness of putative therapies or their relevance to DMD.MethodsAccordingly, we have measured the main cellular components of muscle growth and regeneration over the period of postnatal growth and early pathology in mdx and wild-type (WT) mice; phalloidin bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
135
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(164 citation statements)
references
References 73 publications
19
135
1
Order By: Relevance
“…Because myotonia is measured by assaying individual bundles of fibers, we hypothesized that some regions of muscle may be rescued and not others, and that any potential change in isoform composition in these regions may be diluted in analyses of bulk tissue. This is consistent with a roughly ∼2.5-fold increase in myonuclei per fiber over the first 4 weeks of post-natal development, which could also dilute the proportion of myonuclei containing AAV episomes (Duddy et al, 2015). AAV6-delivered dSaCas9 distribution in EDL fibers revealed mosaic expression, with rare fibers showing region-specific nuclear signal for dCas9 (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Because myotonia is measured by assaying individual bundles of fibers, we hypothesized that some regions of muscle may be rescued and not others, and that any potential change in isoform composition in these regions may be diluted in analyses of bulk tissue. This is consistent with a roughly ∼2.5-fold increase in myonuclei per fiber over the first 4 weeks of post-natal development, which could also dilute the proportion of myonuclei containing AAV episomes (Duddy et al, 2015). AAV6-delivered dSaCas9 distribution in EDL fibers revealed mosaic expression, with rare fibers showing region-specific nuclear signal for dCas9 (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Our approach used systemically delivered AAV, which revealed regional variation in transduction efficiency, likely because NLS-tagged Cas9 protein remained restricted to myonuclear domains transduced by AAV episomes, and many new myonuclei are recruited to fibers throughout postnatal muscle development (Duddy et al, 2015). Previous studies with AAV-mediated gene therapy typically evaluate expression of proteins that can spread throughout muscle fibers, precluding measurement of transduction efficiency to all myonuclei.…”
Section: Discussionmentioning
confidence: 99%
“…, the almost complete loss of the full-length Dp427 isoform of dystrophin is the underlying pathobiochemical defect that triggers progressive fiber degeneration [73], a crucial secondary alteration in dystrophinopathy is presented by extensive myofibrosis [74]. Thus, in addition to central nucleation, rounded fibers, altered myofiber sizes, inflammation, fiber branching, necrosis, and fatty deposition [75], the progressive accumulation of extracellular matrix components plays a major role in contractile weakness [76]. Due to a hyperactive connective tissue, collagens and associated proteins of the extracellular matrix accumulate in dystrophic muscles causing tissue scarring and the loss of skeletal muscle elasticity [77].…”
Section: Resultsmentioning
confidence: 99%
“…In the first 3 weeks, muscle precursor cells (also known as myoblasts or satellite cells) proliferate and fuse with the rapidly elongating myofibres to provide new myonuclei (hyperplasia) (Fig. 1a) [26, 27]. From 3 to 8 weeks of age, rapid hypertrophy results in a 3-fold increase in the myofibre size [26].…”
Section: Introductionmentioning
confidence: 99%
“…From 3 to 8 weeks of age, rapid hypertrophy results in a 3-fold increase in the myofibre size [26]. This increase in sarcoplasmic volume continues until at least 14 to 28 weeks of age [27]. Early autoradiography studies tracking the in vivo kinetics of myoblast proliferation and fusion in healthy muscles of mice aged 6–8 weeks confirmed that most satellite cells were quiescent at this age [28].…”
Section: Introductionmentioning
confidence: 99%